The Effect of Hydroponic Nutrient Sources and Planting Media Types on the Growth and Production of Chinese Kale (Brassica oleraceae L.) - Octavia Zuhrotun Nafiah; Pangesti Nugrahani; Makhziah Makhziah (The University of Lampung, 2023)
Kale is prospective for cultivation because they have a good market. In order to get optimal plant output when growing kale in a hydroponic system, care must be taken to employ AB Mix nutrients and specific planting media types. This study aim at obtaining the right combination of AB Mix nutrients and types of growing media on the yield and growth of Kale plants, which were grown on substrates hydroponic. The study was organized in a Randomized Complete Block Design, with three replicates and factorial arrangement. The first factor was the source of nutrition AB Mix i.e. Infarm, Growrich, and Purie Garden. The second factor was the type of planting media, including husk charcoal, cocopeat, and a mixture of cocopeat and husk charcoal (1:1). Results revealed that the combination treatment of AB Mix nutrients and types of growing media was statistically different on the leaf area. The best combination was between charcoal and Infarm. The source of nutrition AB Mix significantly affected plant growth parameters such as plant height, leaf area, and dry weight of root with Infarm was found to the best nutrient. The type of growing media did not significantly influence all the parameters observed. Interaction between the type of nutrient AB Mix and type of growing media on the leaf area parameter showed with the best result M2A2 (husk charcoal + Infarm) of 700,96 cm2 , but not significantly different from the other treatment. Keywords: AB Mix nutrient, Cocopeat, Husk charcoal, Kale